Bad Luck And Trouble: Jack Reacher # 11 - Child, Lee; Hill, Dick (New York, New York : Books On Tape, 2007)
When a man is killed by being thrown from a helicopter high over the California desert, Jack Reacher discovers that someone is targeting his old friends and teammates and launches a personal campaign to end the conspiracy.
"A Jack Reacher novel"--Container.
Compact discs.
Read by Dick Hill.
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Talking books; Audiobooks